Reduced Graphene Oxide Micromesh Electrodes for Large Area, Flexible, Organic Photovoltaic Devices. (28th January 2015) - Konios, Dimitrios; Petridis, Constantinos; Kakavelakis, George; Sygletou, Maria; Savva, Kyriaki; Stratakis, Emmanuel; Kymakis, Emmanuel
Abstract : A laser‐based patterning technique—compatible with flexible, temperature‐sensitive substrates—for the production of large area reduced graphene oxide micromesh (rGOMM) electrodes is presented. The mesh patterning can be accurately controlled in order to significantly enhance the electrode transparency, with a subsequent slight increase in the sheet resistance, and therefore improve the tradeoff between transparency and conductivity of reduced graphene oxide (rGO) layers. In particular, rGO films with an initial transparency of ≈20% are patterned, resulting in rGOMMs films with a ≈59% transmittance and a sheet resistance of ≈565 Ω sq −1, that is significantly lower than the resistance of ≈780 Ω sq −1, exhibited by the pristine rGO films at the same transparency. As a proof‐of‐concept application, rGOMMs are used as the transparent electrodes in flexible organic photovoltaic (OPV) devices, achieving power conversion efficiency of 3.05%, the highest ever reported for flexible OPV devices incorporating solution‐processed graphene‐based electrodes. The controllable and highly reproducible laser‐induced patterning of rGO hold enormous promise for both rigid and flexible large‐scale organic electronic devices, eliminating the lag between graphene‐based and indium–tin oxide electrodes, while providing conductivity and transparency tunability for next generation flexible electronics. Abstract : A direct laser writing technique is demonstrated for the fabrication of reduced graphene oxide micromesh electrodes with high conductivity and transparency. Their utilization as the transparent electrode in flexible organic photovoltaic (OPV) devices leads to a power conversion efficiency of 3.05%, which is the highest ever reported for flexible OPVs based on solution‐processed graphene electrodes.